2021
DOI: 10.1002/gj.4102
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic expression of the Lenglong Ling area, eastern Qilian Shan, and its coupling relationship with the deep structures

Abstract: Located at the outer edge of the northeastern Tibetan Plateau, the Qilian Shan has long been considered to be the key area to address the issue of how the Tibetan Plateau generates its high topography. However, in spite of the fruitful achievements on the growth pattern and subtle crustal structures of the Qilian Shan, what we know about the regional topography evolution and its relationship with the deep structures are still lacking. In this study, the landscape features of the eastern Qilian Shan and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Fixing the concavity index at a certain plausible value prior to the regression is a viable solution. The value of the concave index, 𝜃𝜃, generally has a range of 0.4-0.5 [26,27], and many previous studies had therefore adopted 0.45 as a fixed value of the concavity index, to obtain the steepness indices from regression [5,14,[29][30], where those obtained are termed as the normalized steepness index ( 𝑘𝑘 𝑠𝑠𝑠𝑠 ). This study also adopted 0.45 as the concavity index.…”
Section: Longitudinal Profile and Normalized Steepness Index (𝑘𝑘 𝑠𝑠𝑠𝑠 )mentioning
confidence: 99%
See 3 more Smart Citations
“…Fixing the concavity index at a certain plausible value prior to the regression is a viable solution. The value of the concave index, 𝜃𝜃, generally has a range of 0.4-0.5 [26,27], and many previous studies had therefore adopted 0.45 as a fixed value of the concavity index, to obtain the steepness indices from regression [5,14,[29][30], where those obtained are termed as the normalized steepness index ( 𝑘𝑘 𝑠𝑠𝑠𝑠 ). This study also adopted 0.45 as the concavity index.…”
Section: Longitudinal Profile and Normalized Steepness Index (𝑘𝑘 𝑠𝑠𝑠𝑠 )mentioning
confidence: 99%
“…In the present study, 𝜒𝜒 was calculated using the TopoToolbox of MatLab's library [31]. To avoid the influence of sedimentation in the Kuninaka Plain (alluvial plain), the starting point for the integration of Equation ( 5) was set to an elevation of 70 m. The 𝑚𝑚/𝑛𝑛 value of the calculated 𝜒𝜒 is 0.45 [5,14,[29][30], the same as that used to calculate 𝑘𝑘 𝑠𝑠𝑠𝑠 .…”
Section: 3𝜒𝜒 Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that, in cases of asymmetric uplift, the main divide moved from a slower uplift basin to a faster uplift basin, and observed a linear correlation between the differences in erosion rate and the divide migration rate, eventually reaching a quasi-steady state during asymmetric uplift [10,11,13]. Although several recent studies on natural landforms affected by asymmetric uplift have been conducted to elucidate the history of landform formation processes along with divide migration [3,[14][15][16], further research is required for a deeper understanding of divide migration affected by asymmetry or heterogeneous uplift. Sado Island, located in the Sea of Japan near Honshu Island (the largest island in Japan), is a tectonically active area.…”
Section: Introductionmentioning
confidence: 99%